MEMBANGUN KOMPETENSI PEMIMPIN DALAM MENGELOLA ORGANISASI PUBLIK: STRATEGI DAN APLIKASI - Nurul Fitriyah; Agus Suliyadi (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
public sector organizations. Competency means capable, capable. Manage competence means leadership skills in managing, managing from planning, coordinating, actualize and oversee public organizations. The competencies that must be owned by the leadership public is at least seven competencies, namely: competence self-manage, competence managing communication, competence of managing plurality, competence of managing ethics, competence managing teams, competing in managing cultural diversity, and competing in managing change. There are at least four strategies to be done: a public leader must think and act generalist, keep learning, put forward an integralistic, strategic way of thinking and oriented to problem solving and public leadership must be fully concentrative. Behavior that must be done public leadership in managing communication is as follows: first, "codification in message delivery Second, appropriate in the delivery of messages according to in-depth knowledge of background, level of education and position of apparatus government in both public and external organizations. Third, use and develop open communication system. Fourth, organize media information needed by employees and fifth, encouraging the emergence of feed back. Strategies that might be applied by the leadership of public organizations in managing pluralism is: the public leadership must be able to as coordinator and intregator of various organizational components so that it can move as a totality and not let the way thinking and acting are fragmented. Some of the steps a sector leader must have public in managing this ethics. public leaders must develop an open system, putting service as the main focus in the public sector, accountable, more responsive and assertive. Steps to be taken by public leaders in managing teams are minimal two things: keeping the cohesion between members one with another and as mediator. The strategy that leaders of public organizations must take in managing cultural diversity is as follows: cultural differences must be seen as a wealth which should be developed not as a threat. These positive values ​​will be made input in advancing the organization. On the other hand leaders of public organizations should be able to as integrator. The attitude that must be applied by the public leadership in managing this change is: public leaders must have a high adaptability attitude and public leadership must flexible.